2020
DOI: 10.3390/jcm9041057
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition Abilities in Adults with Anorexia Nervosa are Associated with Autistic Traits

Abstract: Difficulties in socio-emotional functioning are proposed to contribute to the development and maintenance of anorexia nervosa (AN). This study aimed to examine emotion recognition abilities in individuals in the acute and recovered stages of AN compared to healthy controls (HCs). A second aim was to examine whether attention to faces and comorbid psychopathology predicted emotion recognition abilities. The films expressions task was administered to 148 participants (46 AN, 51 recovered AN, 51 HC) to assess emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 92 publications
(118 reference statements)
2
22
0
Order By: Relevance
“…Past research has suggested considerable heterogeneity in social- and neuro-cognitive functioning in individuals with AN, possibly indicating differences in aetiological or maintenance factors (Renwick et al 2015 ). Our results suggest that reduced social attention in AN may be a result of high ASD traits, in accordance with recent research demonstrating differences in set-shifting, emotion recognition, and empathic abilities in individuals with AN with and without high ASD traits (Kerr-Gaffney et al 2020a , c ; Westwood et al 2017b ). In order to clarify the mixed findings in related domains, future work examining social cognition in individuals with AN may benefit from including a measure of ASD traits, or indeed a sub-group of individuals with AN and a confirmed diagnosis of ASD.…”
Section: Discussionsupporting
confidence: 92%
“…Past research has suggested considerable heterogeneity in social- and neuro-cognitive functioning in individuals with AN, possibly indicating differences in aetiological or maintenance factors (Renwick et al 2015 ). Our results suggest that reduced social attention in AN may be a result of high ASD traits, in accordance with recent research demonstrating differences in set-shifting, emotion recognition, and empathic abilities in individuals with AN with and without high ASD traits (Kerr-Gaffney et al 2020a , c ; Westwood et al 2017b ). In order to clarify the mixed findings in related domains, future work examining social cognition in individuals with AN may benefit from including a measure of ASD traits, or indeed a sub-group of individuals with AN and a confirmed diagnosis of ASD.…”
Section: Discussionsupporting
confidence: 92%
“…Although several studies have shown that the perception of social stimuli is altered in individuals with ASD or autistic traits [16,17,23,25,26] these studies only used neutral social stimuli. Mental processing in individuals with ASD [27] or autistic traits [28,29] has been found to differ depending on the emotional valence of the stimulus, in that such individuals exhibit worse recognition of stimuli with negative rather than positive emotional valence. However, very little is known of the cognitive and neural mechanisms involved in the processing of social-emotional stimuli-a process that is fundamental to human communication [30]-in individuals with autistic traits.…”
Section: Introductionmentioning
confidence: 99%
“…To address this important health issue, the current Special Issue collected 21 articles examining the most recent and relevant scientific findings regarding advances in ED. The published articles comprised three reviews and 18 research articles focusing on different aspects, such as genetic [ 7 ] and epigenetic factors [ 8 ], biomarkers [ 9 ], comorbidity [ 10 , 11 , 12 , 13 , 14 ], clinical phenotypes [ 15 , 16 ], neurocognition [ 12 , 17 , 18 , 19 , 20 , 21 ], treatment predictors [ 22 ], and treatment models and therapeutic targets [ 19 , 23 , 24 , 25 , 26 , 27 ]. Altogether, these studies may provide increased knowledge about the pathogenesis, the risk factors, the maintenance factors, and the most appropriate treatments tools for ED.…”
mentioning
confidence: 99%
“…In addition, understanding the role that comorbid autistic features play in patients with AN is also interesting. Therefore, Kerr-Gaffney et al [ 13 ] compared the emotion recognition abilities and attention to faces using eye-tracking in patients with AN and healthy control, concluding that difficulties in emotion recognition appear to be associated with high comorbid autistic traits rather than with a phenotypic feature of AN, independent of illness state. In the same vein, Kinnaird et al [ 14 ] explored the use of a brief sensory sensitivity screener in patients with AN, to assess whether self-rated sensory sensitivity is related to autistic traits.…”
mentioning
confidence: 99%
See 1 more Smart Citation